Structure of epipelagic and pelagic copepod communities in the Kuantan river, estuary (east coast of peninsular Malaysia) and adjacent coastal water in relation to environmental factors - Rahman, Mustafizur M. (Springer Nature, 2025)
This study explored how environmental variables influence the structure of epipelagic and pelagic copepod communities across tropical rivers, estuaries, and coastal ecosystems, considering the ongoing challenge of understanding the effects of these variables on copepod ecology in various tropical aquatic environments. Environmental variables were measured monthly over a complete 12-month cycle in the epipelagic (0.3 m below the surface) and pelagic (3.0 m below the surface) waters of the Kuantan River, which included two zones: downstream and upstream, as well as in its estuary and the nearest coast. This was done simultaneously with copepod data collection. Key findings indicated a total of 46 copepod species from 13 families were recorded. The highest species count was found at the coast (37 species), followed by the estuary (29), downstream (26), and upstream (18). Oithonoid copepods were dominant across all sampling zones (coast, 9.48 × 103 individuals m⁻3, 28.3% of total copepods; estuary, 9.88 × 103 individuals m⁻3, 30%; downstream, 7.81 × 103 individuals m⁻3, 30.6%), except in the upstream zone, where freshwater cyclopoid copepods dominated (8.14 × 103 individuals m⁻3, 41.9%) and harpacticoid copepods were absent. The average density of total copepods was similar in the coast (33.48 × 103 individuals m−3) and estuary (32.59 × 103 individuals m−3), both of which were greater than downstream (25.50 × 103 individuals m−3), followed by upstream (19.44 × 103 individuals m−3). The copepod species diversity was lower in the upstream zone (0.83) compared to the coast (1.20), estuary (1.17), and downstream (1.10) zones, with no difference among them. Water temperature (average range, 28.90–29.96 °C) negatively influenced the density of all observed copepod groups in all studied environments. Salinity did not limit the abundance of the copepod population at the coast and estuary but was a limiting factor for copepods in the river. The average salinity of as high as 0.97 PSU was harmful to observed freshwater copepod species, while its value ≤ 10.35 PSU performed as a controlling variable for observed marine species. The abundance of phytoplankton directly limited all observed copepod groups and indirectly amplified the negative effects of total suspended solids on cyclopoid and calanoid copepods. The remaining measured environmental factors such as pH, dissolved oxygen, turbidity, alkalinity, and phosphate did not affect the availability of any group of recorded copepods.